States of reality: how democracy levels impact the framing of deepfakes in newspapers and the resultant impact on attitudes - Pillay, Amber Rose (Nanyang Technological University, 2025)
This study investigates how the framing of deepfake technology under different government systems affects public perception and actions. Drawing on media framing theory and political communication literature, content analysis of news articles was employed to identify salient frames and examine linguistic differences. Existing literature on framing of emerging technologies has predominantly situated within Western perspectives, underscoring the focus of this research on democratic and non-democratic countries across Asia. The research explores how different countries frame risks and benefits, moral evaluation and proposed prognostic actions. Results indicate that democratic states tend to focus on risks associated with deepfakes, while non-democratic states leaned towards a more balanced approach, highlighting benefits as well. Subsequently, an experimental survey was conducted to measure the differential impact of these framing strategies on public perception and actions. Results revealed that negative framing of deepfakes led to higher levels of concern, lower support for development and higher support for regulations compared to neutral and positive framing. However, there were no immediate effects on detection abilities. The findings provide insights into the interplay between political systems, media narratives and public perceptions of deepfakes as an emerging AI-driven technology and contribute to growing literature surrounding factors impacting deepfake detection abilities.